STRATEGI MARKETING BJB SYARIAH PADA PRODUK MOBILE MASLAHAH (Studi Kasus di Bank Jabar Banten Syariah Kantor Cabang Pembantu Sumber) - danureja, trisna (MASILE, 2024)
Abstract Mobile Banking services are a form of innovation launched by banks to make customer transactions easier. However, problems often arise in the delivery of strategies that have been designed by banks in introducing this service. One of the main problems is that there are still many customers who do not fully understand this Mobile Banking service, which results in a lack of trust in the security of their data, as happened at Bank Jawa Barat Banten KCP Sumber through the Mobile Maslahah service. The research objective is to determine marketing strategies, obstacles and challenges, and the contribution of Bank BJB Syariah in marketing Maslahah Mobile Products (Case Study of Bank BJB Syariah KCP Sumber). The research method used is field research with a qualitative descriptive approach. The data used in this research are secondary and primary data. The informants in the research were 1 employee and 20 customers. The data collection techniques used were observation, interviews and documentation. The research results show that in the marketing strategy for the Mobile Maslahah product, it was found that the company implemented an approach that refers to general principles in the banking world. This approach involves the concepts of segmentation, targeting, positioning, and marketing mix. The form of the marketing mix includes product, price, place and promotion. Obstacles faced in marketing this product include unstable internet network problems, customer difficulties in using the internet, and lack of customer understanding. In this research, we can also find positive contributions made by Bank BJB Syariah in marketing Mobile Maslahah products, such as efforts to increase customer understanding and solutions to overcome internet network problems. It is important to use these findings as a basis for taking better action in overcoming obstacles and improving Mobile Maslahah product marketing strategies. Keywords: Marketing Strategy, Marketing, Mobile Maslahah